2012
DOI: 10.1159/000332015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Transmitted Drug Resistance in Chronically HIV-Infected Patients in Germany: The RESINA Study 2001–2009

Abstract: Objectives: Transmitted HIV drug resistance may impair treatment efficacy of combination antiretroviral therapy (ART). This study describes the epidemiology of transmitted resistance in chronically infected patients. Methods: In a prospective multicenter trial in Nordrhein-Westfalen, Germany, transmitted drug resistance was determined by genotypic resistance testing in patients on initiation of first-line ART. Results: From 2001 to 2009, 2,078 patients were enrolled in the study. 79.9% were male, 81.2% were Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
0
18
0
4
Order By: Relevance
“…Patients are included in the RESINA cohort at the time of the intended start of ART. Since 2001, RESINA is an ongoing study analyzing epidemiological and immunological data, HIV resistance patterns and therapeutic data in treatment-naive HIV-positive patients – as also described by Oette et al [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Patients are included in the RESINA cohort at the time of the intended start of ART. Since 2001, RESINA is an ongoing study analyzing epidemiological and immunological data, HIV resistance patterns and therapeutic data in treatment-naive HIV-positive patients – as also described by Oette et al [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The study reported an average DRM prevalence of 9.2% in 2001-2009 (NRTIs 5.8%, NNRTIs 2.7%, and PIs 2.7%) in North Rhine-Westphalia, Germany [13]. Moreover, subtype B was predominant (72%) and recombinant forms were found in only 6% of the therapy-naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is the first study on HIV-1 subtype diversity and prevalence of DRMs in therapy-naïve HIV-1-infected children receiving routine care at a center in Germany. This cohort study reveals adifferent HIV-1 subtype distribution with predominant non-B subtype infections versus the therapy-naïve HIV-1-infected adults in the RESINA cohort in Germany [13]. This difference is mainly attributed to the different ethnic backgrounds with a higher proportion of immigrants from sub-Saharan Africa in the pediatric cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it seems that the prevalence of transmitted HIV drug resistance (TDR) has followed a steady pattern in developed countries [49] , recently conducted surveys in western Europe and United States have shown that the trend of TDR has become stable in recent years [50,51] . Increasing efficacy of HAART and development of new generation ARV agents have been proposed as possible reasons for this trend [52][53][54][55] . In some previous studies in developed settings, HIV drug resistance was more common among men who have sex with men (MSM), as well as among individuals with a positive history of STIs, mono-therapy, and NNRTI use [30] .…”
Section: Prevalence and Spatial Distribution Of Ardrmentioning
confidence: 99%